Description of two new species, Aphanolaimus strilliae n. sp. (Nematoda:Aphanolaimidae) and Makatinus africanus n. sp. (Nematoda: Aporcelaimidae), and SEM observations on three known species from freshwater sources in the Telperion Nature Reserve (Mpumalanga, South Africa) - Girgan, Chantelle; Marais, Mariette; Fourie, Hendrika; Tiedt, Lourens; Swart, Antoinette (Zootaxa, 2019)
Aphanolaimus strilliae n. sp. and Makatinus africanus n. sp. are described from freshwater sources in the Telperion Nature Reserve, Mpumalanga, South Africa. Aphanolaimus strilliae n. sp. is characterised by a body length of 1240–1613 μm, more than 800 body annules, lateral field originating between the first and second lateral body pore at the 34th–46th annule, first lateral body pore located at the 25th–35th annule, vagina V-shaped and bent anteriorly, 142–195 µm long uterus and 165–207 µm long tail with spinneret offset. This species is ovoviviparous and no males were found. Makatinus africanus n. sp. is characterised by a large, thick body (3228–4128 μm long, a = 30–39 wide), slightly set off lip region with amalgamated lips; 31–34 μm long odontostyle; long tongue-shaped cardia, and stout, short tail (30–43 μm long) with a small peg / digitate extension and male absent. Populations of three known species, Chronogaster africana, Eutobrilus annetteae and Neotobrilus ampiei, from fresh water at the Telperion Nature Reserve are described and scanning electron microscope graphs of these species published for the first time.